Appearances often deceive in racerunners: integrative approach reveals two new species of Eremias (Squamata: Lacertidae) from Pakistan - Masroor, Rafaqat; Khan, Muazzam Ali; Nadeem, Muhammad Sajid; Amir, Shabir Ali; Khisroon, Muhammad; Jablonski, Daniel (Zootaxa, 2022)
Based on newly provided morphological and previously published genetic data, we describe two new distinctive sympatric lacertid lizards of the genus Eremias (subgenus Aspidorhinus) from the arid mountains of northwestern Balochistan Province, Pakistan. The new species, Eremias killasaifullahi sp. nov. and Eremias rafiqi sp. nov. are distinguished from all other species of the subgenus Aspidorhinus (E. afghanistanica, E. fahimii, E. isfahanica, E. kopetdaghica, E. lalezharica, E. montana, E. nikolskii, E. papenfussi, E. persica, E. regeli, E. roborowskii, E. strauchi, E. suphani, and E. velox) by unique morphological characters and genetic differentiation. In the molecular phylogeny of Aspidorhinus, both new taxa are well-supported lineages differentiated from other species of this subgenus by uncorrected p distances from 8.5% to 21.6%, respectively. Both new species belong to E. persica complex where E. rafiqi sp. nov. is partly similar in dorsal color pattern to E. persica but can be distinguished from this species by unique meristic and morphometric characters. Eremias rafiqi sp. nov. is found in Pakistan, Afghanistan, and eastern Iran. Eremias killasaifullahi sp. nov. can be differentiated from E. persica by its distant distribution, dorsal color and pattern, smaller size, and less number of gulars and ventral scales. Eremias killasaifullahi sp. nov. is only known from the type locality and represents the local microendemism, along with other endemic species of reptiles reported from this part of Pakistan. We, however, expect that E. killasaifullahi sp. nov. could have a broader range in northwestern Pakistan and southeastern Afghanistan, which should be an object of following investigations. Our data show that remote areas between Hindu Kush Mountains and Indus River need attention as they most probably represent possible sources of genetic and species diversity in the region.